Odpowiedzi

Najlepsza Odpowiedź!
2010-03-20T16:50:31+01:00
X*5+x+15-x dla x = 2

x*5+15=25


0,5y-3*2y+5,5+0,5 dla y =1
0,5y-6y+6=6-5,5=0,5

-6x+2y+7+4x-5y-3 dla x= 0,5 y i dla y= 0,1

-2x-3y+4=-1-0,3+4=2,7

2x-6y-4y+8-5x+y-11 dla x =1 i jedna trzecia i dla y= jeden dziewiątych

-3x-9y-3=-4-1-3=-8
2010-03-20T16:56:48+01:00
X*5+x+15-x = 5x + x + 15 - x = 5x + 15 = 5 * 2 + 15 = 10 + 15 = 25

0,5y-3*2y+5,5+0,5 = 0,5y - 6y + 5,5 + 0,5 = -5,5y + 6 = -5,5 + 6 = 0,5

-6x+2y+7+4x-5y-3 = -2x -3y + 4 = -2 * 0,5 - 3 * 0,1 + 4 = -1 - 0,3 + 4 = = -1,3 + 4 = 2,7

2x-6y-4y+8-5x+y-11 = -3x -9y -3 = -3 * 1 1/3 - 9 * 1/9 - 3 = -4 -1 - 3 = = -8
2010-03-20T16:57:38+01:00
2*5+2+15-2=10+2+13=25
(0,5*1)-3*(2*1)+5,5+0,5=0,5-(-1)+6=7,5
-6*0,5+2*0,1+7+4*0,5-5*0,1-3=-3+0,2+7+(-2,5)